The experiences of family resilience from the view of the adult children of parents with bipolar disorder in Chinese society. (7th August 2021) - Liu, Sara Hsin‐Yi; Hsiao, Fei‐Hsiu; Chen, Shing‐Chia; Shiau, Shu‐jen; Hsieh, Ming H.
Abstract: Aims: This study explored how adult children perceived family resilience, barriers to develop family resilience and how cultural values influence their experience of parents with bipolar disorder in Chinese society. Design: A qualitative design with an interpretive phenomenological analysis of data was employed. Methods: Twenty adults who had lived with parents with bipolar disorder during childhood were recruited from the acute psychiatric ward when their parents were admitted to the hospital. They described their experiences of perceived family resilience and barriers to resilience (October 2013–September 2015). Semi‐structured interviews were conducted in the hospital meeting room or at a convenient location. Findings: Six themes were identified in family resilience: ill parents try to be good parents, parents' personal strengths, parents' positive attitudes towards mental illness, flexibility of family role, cohesive relationships between family members, and families' social connections. Three themes were identified in the barriers to develop family resilience: poor parenting/family function, conflict between parents and poor mental health literacy. Conclusion: Children's views of family resilience could transform their suffering from lived experiences with a mentally ill parent to a positive growth experience. Family resilience includes well and ill parents' efforts and social network's help to maintain family function. However, the conflicts between well and ill parents and poor family function result in a traumatic growth experience. Impact: To enhance a positive growth experience, family resilience programs for a parent with bipolar disorder aiming to cultivate both the ill and well parents' inner strength and their competence of parenting skills with connecting their social network to maintain family function is needed. Moreover, early stress‐reduction intervention needs to be developed for children who did not experience family resilience.